The Impact of Arabidopsis on Human Health: Diversifying Our Portfolio - Jones, Alan M. (2008)
Studies of the model plant Arabidopsis thaliana may seem to have little impact on advances in medical research, yet a survey of the scientific literature shows that this is a misconception. Many discoveries with direct relevance to human health and disease have been elaborated using Arabidopsis, and several processes important to human biology are more easily studied in this versatile model plant.